Analysis of Syntactical Errors and Mistakes in Students’ Writing (RETAIN, 2018)
Abstract Written language is difficult for some people especially some learners who learn English as foreign language, because it somehow has a complicated syntactical form that is hard to be understood. Thus, it causes error and mistake. Commonly, error occurs because learners do not realize that they made error and it is the gaps in learners knowledge of the target language especially English. In particular, the purpose of this research is to describe kinds of syntactical error and mistake found in students’ writing composition, namely in paragraph writing class of university students in second semester. Dealing with the research questions and objectives of the study in the first chapter, the data gained are going to be analyzed qualitatively. The data of the study were obtained from students’ errors and mistakes. In this study, the data were obtained from the form of words, phrases, and sentences found in the students’ writing composition. The source data were collected through the students’ writing composition. Based on the result, it can be seen that there are five types of syntactical errors and mistakes that made by students, those are: word order, omitted word, unnecessary word, run-on sentence, and fragments. In this result, most of the students made an error since they did not know to answer the correct one.Keywords: Analysis Error and Mistake, Syntactical Deviation, Student Writing Composition. AbstrakBahasa tulisan sulit bagi sebagian orang terutama bagi para pelajar yang belajar bahasa inggris sebagai bahasa asing, karena terkadang memiliki bentuk sintaktis yang sulit untuk dipahami. Demikian, ini menyebabkan kesalahan dan keliruan. Pada umumnya, kesalahan terjadi karena para pelajar tidak menyadari bahwa mereka melakukan kesalahan and ini adalah celah untuk pengetahuan para pelajar pada bahasa asing khususnya Bahasa Inggris. Khususnya, tujuan pada penelitian ini adalah untuk menggambarkan macam-macam “syntactical error and mistake” yang ditemukan di tulisan-tulisan para pelajar, yaitu di kelas Pargarph Writing pada Mahasiswa di Semester Kedua. Berhubungan dengan rumusan masalah dan tujuan penelitian pada bab pertama. Data yang telah diperoleh akan dianalisis melalui penelitian kualitatif. Data pada penelitian ini diperoleh dari para kesalaha and kekeliruan Mahasiswa dan data itu diperoleh dari kata-kata, tutur kata, dan kalimat-kalimat yang telah ditemukan pada tulisan Mahasiswa. Sumber data didapatkan melalui tulisan Mahasiswa. Berdasarkan dari penelitian, daat terlihat bahwa terdapat lima macam “syntactical errors and mistakes” yang dibuat oleh para pelajar, diantaranya: “word order, omitted word, unnecessary word, run-on sentence, and fragments.” Pada penelitian ini para pelajar melakukan kesalahan dikarenakan mereka tidak memahami untuk menjawab yang benar.Kata kunci: Menganalisis Kesalahan dan Kekeliruan, Penyimpangan Sintaktis, Komposisi Tulisan Mahasiswa.